Efficacy and safety of non-pharmacological, pharmacological and surgical treatments for hand osteoarthritis in 2024: a systematic review - Féline P B Kroon; Margreet Kloppenburg; Ida K Haugen; Ingvild Kjeken; Nina Østerås; Anne Therese Tveter; Geir Smedslund; Daniel Huseby Bordvik; Kristine Aasness Fjeldstad; Ingrid Skaalvik (RMD Open)
Background We aimed to update the 2018 systematic literature review on the efficacy and safety of treatments for hand osteoarthritis (OA), which was based on 126 studies.Methods We performed a systematic literature search on randomised controlled trials from June 2017 up to 31 December 2023. Risk of bias was assessed using the RoB2 tool. Meta-analyses of previous and new studies regarding the efficacy for pain, function, grip strength and OMERACT/OARSI responders were performed. Certainty of evidence was judged using the GRADE (Grading of Recommendations Assessment, Development and Evaluation) tool.Results Sixty-five new studies were included. For non-pharmacological interventions, there was low-certainty evidence for a small long-term effect of hand exercises and a moderate long-term effect of thumb orthoses for pain, and moderate-certainty evidence that assistive devices had a moderate long-term effect on function. Concerning pharmacological interventions, there was low-certainty evidence for a moderate short-term effect of oral non-steroidal anti-inflammatory drugs (NSAIDs) on pain, high- and moderate-certainty evidence for a small short-term effect of topical NSAIDs and oral glucocorticoids on function, respectively, and low-certainty evidence that oral glucocorticoids had a small short-term effect on function. Further, there was low-certainty evidence that methotrexate had a small long-term effect on pain. The heterogeneity of studies did not allow for any meta-analyses on surgery.Conclusion The results largely support current treatment recommendations. However, there is a lack of interventions that efficiently improve grip strength, and the evidence for most current treatments is still limited. To better understand action mechanism of different treatments, future trials should include hand OA subtyping and be powered for subgroup analyses.